A novel experimental setup for energy loss and charge state measurements in dense moderately coupled plasma using laser-heated hohlraum targets. (March 2016) - Ortner, A.; Schumacher, D.; Cayzac, W.; Frank, A.; Basko, M.M.; Bedacht, S.; Blazevic, A.; Faik, S.; Kraus, D.; Rienecker, T.; Schaumann, G.; Tauschwitz, An.; et al.
Abstract: We report on a new experimental setup for ion energy loss measurements in dense moderately coupled plasma which has recently been developed and tested at GSI Darmstadt. A partially ionized, moderately coupled carbon plasma ( ne ≤ 0.8 10 22 cm -3, Te = 15 eV, z = 2.5, Γ = 0.5) is generated by volumetrical heating of two thin carbon foils with soft X-rays. This plasma is then probed by a bunched heavy ion beam. For that purpose, a special double gold hohlraum target of sub-millimeter size has been developed which efficiently converts intense laser light into thermal radiation and guarantees a gold-free interaction path for the ion beam traversing the carbon plasma. This setup allows to do precise energy loss measurements in non-ideal plasma at the level of 10 percent solid-state density.